2016
DOI: 10.1080/14789450.2017.1265450
|View full text |Cite
|
Sign up to set email alerts
|

Progress and pitfalls in finding the ‘missing proteins’ from the human proteome map

Abstract: The Human Proteome Project was launched with two main goals: the comprehensive and systematic definition of the human proteome map and the development of ready to use analytical tools to measure relevant proteins in their biological context in health and disease. Despite the great progress in this endeavour, there is still a group of reluctant proteins with no, or scarce, experimental evidence supporting their existence. These are called the 'missing proteins' and represent one of the biggest challenges to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…those still in P2 to P5) that remain refractory to tryptic peptide verification at the necessary stringency. This aspect has been the subject of several recent reviews and so does not need expanding here 18, 19 .…”
Section: Existence Evidencementioning
confidence: 99%
“…those still in P2 to P5) that remain refractory to tryptic peptide verification at the necessary stringency. This aspect has been the subject of several recent reviews and so does not need expanding here 18, 19 .…”
Section: Existence Evidencementioning
confidence: 99%
“…Using TAILS and thus specifically focusing on protein N-termini allowed the researchers to substantially reduce sample complexity in order to improve the detection of low-abundance proteins. In this way, the authors were able to identify 1369 N-terminal peptides from 1234 proteins, 281 of which were novel erythrocyte proteins while six previously-missing proteins [172,173] were identified by MS for the first time [174]. The same group also analyzed human dental pulp as a unique tissue that could lead to the identification of additional missing proteins, and found that most of the identified N-termini represented proteolytic cleavage sites [175].…”
Section: Analyzing Endogenous Proteolytic Cleavage (Proteolysis) In Cmentioning
confidence: 99%
“…However, insufficient coverage may also be important for novel peptides or for isoform detection [57]. (iii) Highly hydrophobic proteins (such as olfactory receptors, membrane proteins and highly insoluble proteins), which are estimated to represent 20–30% of the total encoded human proteome, are notoriously difficult to identify by MS [5861]. (iv) The MPs may result from low-resolution mass analysis [59] (v) Rare proteins are produced only at specific times and in specific cells.…”
Section: Challenges For the C-hppmentioning
confidence: 99%